2017
DOI: 10.1249/mss.0000000000001200
|View full text |Cite
|
Sign up to set email alerts
|

ASC Methylation and Interleukin-1β Are Associated with Aerobic Capacity in Heart Failure

Abstract: Background Aerobic capacity, as measured by peak oxygen uptake (V̇O2), is one of the most powerful predictors of prognosis in heart failure (HF). Inflammation is a key factor contributing to alterations in aerobic capacity, and interleukin (IL)-1 cytokines are implicated in this process. The adaptor protein ASC is necessary for inflammasome activation of IL-1β and IL-18. ASC expression is controlled through epigenetic modification; lower ASC methylation is associated with worse outcomes in HF. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…Other studies have demonstrated hypermethylation of the ASC gene in heart failure patients and in older individuals after exercise, and in turn, methylation was related to decreased expression of ASC and IL-1 family. Therefore, exercise may play an important role in the epigenetic modification of the ASC gene [8,9,17,18]. Although in this study we did not measure IL-1β or IL-18 expression, we quantified both cytokines; however, no significant differences were found probably because our study population did not have another metabolic disease.…”
Section: Discussionmentioning
confidence: 88%
“…Other studies have demonstrated hypermethylation of the ASC gene in heart failure patients and in older individuals after exercise, and in turn, methylation was related to decreased expression of ASC and IL-1 family. Therefore, exercise may play an important role in the epigenetic modification of the ASC gene [8,9,17,18]. Although in this study we did not measure IL-1β or IL-18 expression, we quantified both cytokines; however, no significant differences were found probably because our study population did not have another metabolic disease.…”
Section: Discussionmentioning
confidence: 88%
“…Human embryonic kidney cells infected with Mycobacterium tuberculosis H37Rv reduced NLRP3 promoter region methylation and then activated NLRP3 inflammation, resulting in upregulation of the RNA level of NLRP3 and IL-1β ( 41 ). The VO2 max of heart failure patients was positively related to the level of the ASC average methylation level and negatively correlated with the plasma concentration of IL-1β ( 42 ). These studies indirectly supported our observations of relationships between NLRP3, AIM2, and ASC methylation level changes and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated hypermethylation of the ASC gene in heart failure patients and in older individuals after exercise, and in turn, methylation was related to decreased expression of ASC and IL-1 family. Therefore, exercise may play an important role in the epigenetic modi cation of the ASC gene [8,9,17,18]. Although in this study we did not measure IL-1β or IL-18 expression, we quanti ed both cytokines; however, no signi cant differences were found probably because our study population did not have another metabolic disease.…”
Section: Discussionmentioning
confidence: 90%